Collaborative governance in the development of local economic resources in Sumenep Regency - Rillia aisyah haris; Ida Syafriyani; Nur Inna Alfiyah (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
Local economic development is currently very intensively carried out in several regions in Indonesia. Local economic development is believed to be a holistic perspective to address regional economic problems based on local resources. Sumenep Regency is one of the regencies in East Java, which is currently developing several of Sumenep's superior agricultural commodities consisting of shallots, chili herbs, and Moringa into processed products that have added value to improve the community's economy. This research studies efforts to develop local economic resources in Sumenep Regency from a Collaborative Governance perspective, including initial conditions, leadership, institutional design, and collaboration processes. This study used a qualitative method. Interviews, documentation, and observation were used in data collection. The research results showed that adequate initial conditions have supported collaborative Governance in the development of local economic resources. However the collaboration process needs to be managed properly. This study recommends strengthening collaborative institutional designs and facilitative leadership on all fronts.